Green synthesis and characterization of silver nanoparticles using aqueous extract of marsilea minuta linn and evaluation of its antioxidant and antibacterial activities - LOGAPRAKASH KULOTHUNGAN,; UMA RAMASWAMY, (International Journal of Pharma and Bio Sciences, 2018)
Nanoparticles of silver nitrate are receiving increasing attention due to their widespread applications. The present study deals with the biosynthesis and characterization of silver nanoparticles (AgNPs) using aqueous leaf extract of Marsilea minuta Linn and its antioxidant and antibacterial activities. Parameters like concentrations of reactants, silver nitrate and whole plant extract were standardized to produce silver nanoparticles at 37°C.The maximum synthesis of AgNP was obtained in 5% plant extract, pH 7 and 1and 3 mM silver nitrate within 30 minutes at 37°C. AgNPs were characterized by using UV-visible Spectroscopy, Scanning electron microscopy and Fourier Transform Infrared spectroscopy. Silver Surface Plasmon Resonance (SPR) occurred at 437 nm for 1and 3 mM AgNP’s. SEM analysis showed the presence of nanoparticles in spherical shape and dispersed and the size ranged from 53-95 nm. The FTIR spectra revealed the presence of reducing groups in the extract responsible for AgNP synthesis. The synthesized AgNPs exhibited super oxide, hydroxyl radical scavenging and ferrous chelating activities. The AgNPs exhibited antibacterial activity against pathogenic bacteria Staphylococcus aureus, Klebseilla pneumonia, Entercoccus faecalis, Salmonella typhi and Bacillus subtilis which was analysed by Disc diffusion method. Antioxidant and antibacterial activity of AgNP’s of Marsilea minuta showed maximum activity in 3mMAgNP. Ferrous chelating and hydroxyl radical activity was observed in AgNP’s (3mM) of M.minuta with an IC50 value of 100 & 500µg respectively. The highest zone of inhibition was observed in 3mM AgNP’s of M.minuta against Klebseilla pneumonia and Entercoccus faecalis with an inhibition zone of 13.3 and 13.0 mm respectively.